Heat-enhanced peptide synthesis on Teflon-patterned paper. Issue 22 (17th May 2016) - Deiss, Frédérique; Yang, Yang; Matochko, Wadim L.; Derda, Ratmir
Abstract : In this report, we describe the methodology for 96 parallel organic syntheses of peptides on Teflon-patterned paper assisted by heating with an infra-red lamp. Abstract : In this report, we describe the methodology for 96 parallel organic syntheses of peptides on Teflon-patterned paper assisted by heating with an infra-red lamp. SPOT synthesis is an important technology for production of peptide arrays on a paper-based support for rapid identification of peptide ligands, epitope mapping, and identification of bio-conjugation reactions. The major drawback of the SPOT synthesis methodology published to-date is suboptimal reaction conversion due to mass transport limitations in the unmixed reaction spot. The technology developed in this report overcomes these problems by changing the environment of the reaction from static to dynamic (flow-through), and further accelerating the reaction by selective heating of the reaction support in contact with activated amino acids. Patterning paper with Teflon allows for droplets of organic solvents to be confined in a zone on the paper array and flow through the paper at a well-defined rate and provide a convenient, power-free setup for flow-through solid-phase synthesis and efficient assembly of peptide arrays. We employed an infra-red (IR) lamp to locally heat the cellulosic support during the flow-through delivery of the reagents to each zone of the paper-based array. We demonstrate that IR-heating in solid phase peptide synthesis shortened the reaction time necessary for amide bond formation down to 3 minutes; in some couplings of alpha amino acids, conversion rates increased up to fifteen folds. The IR-heating improved the assembly of difficult sequences, such as homo-oligomers of all 20 natural amino acids.